ANALISIS PENGARUH KOMPENSASI, KOMITMEN ORGANISASIONAL, DAN KEPEMIMPINAN TERHADAP TURNOVER INTENTION (STUDI PADA PERUSAHAAN X) - Puspasari, Orchita; Nugraheni, Rini (Diponegoro Journal of Management, 2016)
Turnover intention is common term we hear every day, especially in  X Company. The occurrence of turnover intention phenomenon is influenced by some factors such as compensation, organizational commitment, and leadership. This study aimed to analysing influence of compensation, organizational commitment, and leadership on turnover intention .In this study data were collected by spreading quationnaires to 60 employees in X Companies. Technique of data testing used was multiple linear regression.The result of the study shows that compensation, organizational commitment, and leadership negatively and significantly influence turnover intention in X Company. The result of the study shows that data has been qualified to be used as the multiple linear regression model. Based on the result Turnover Intention = -0.324 Compensation -0.306 Organizational Commitment -0.300 Leadership. The hypohtesis testing the writer concluded that: Compensation has significant and negative effect on Turnover Intention, Organizational Commitment has significant and negative effect on Turnover Intention, and Leadership has significant and negative effect on Turnover Intention. The value of Ajusted R Square is 31.6 % this means that the amount of influence   exerted   by   variables   Compensation, Organizational Commitment, and Leadership to  the changes that occur in the Turnover Intention is 31.6 % , while the 68.4% is explaining by other variables outside the model.